Medical technologies in intraoperative pressure ulcers: A literature review - San Juan, Daniel; Miranda, Raul Alejandro; Pascacio, Antonio Alonso; Mayorquin, Sergio; Sosa, Miguel Ángel (Medicina e Investigación Universidad Autónoma del Estado de México, 2020)
ABSTRACT Pressure ulcers (PU) are ischemic lesions of the tissues that arise primarily as a result of compressive and shear forces between the skin and a rigid surface. It is currently considered a public health problem, quite often as a complication during the surgical period. There are known intrinsic and extrinsic risk factors that predispose the population to these lesions. Several preventive measures have been developed for the three phases of the surgical process: Preoperative, intraoperative, and postoperative. Few studies have addressed the technological developments in the preventive measures of the PU as a potential assessment of such lesions. This article aims to review the main concepts in the framework of PU, risk factors, therapeutic approach, and recent technological advances in the prevention of PU in the intraoperative period. We found that is necessary to redouble efforts to reduce PU incidence during a surgical procedure, insufficient evidence and no definitive solutions is existing nowadays even though some contributions and studies have been made to enhance technological development in terms of PU prevention. RESUMEN Las úlceras por presión (UP) son lesiones isquémicas de los tejidos que surgen principalmente como resultado de las fuerzas de compresión y cizallamiento entre la piel y una superficie rígida. En la actualidad se considera un problema de salud pública, a menudo como una complicación durante el periodo quirúrgico. Se conocen factores de riesgo intrínsecos y extrínsecos que predisponen a la población a sufrir estas lesiones. Se han desarrollado varias medidas preventivas para las tres fases del proceso quirúrgico: Preoperatoria, intraoperatoria y postoperatoria. Pocos estudios han abordado los desarrollos tecnológicos en las medidas preventivas de las UP como potencial evaluación de dichas lesiones. Este artículo pretende revisar los principales conceptos en el marco de las UP, los factores de riesgo, el enfoque terapéutico y los recientes avances tecnológicos en la prevención de las UP en el periodo intraoperatorio. Encontramos que es necesario redoblar los esfuerzos para reducir la incidencia de las UP durante un procedimiento quirúrgico, no existiendo en la actualidad evidencias suficientes ni soluciones definitivas, aunque se han realizado algunas aportaciones y estudios para potenciar el desarrollo tecnológico en materia de prevención de las UP.